2009
DOI: 10.1371/journal.pone.0006401
|View full text |Cite
|
Sign up to set email alerts
|

Sex Determination in the Squalius alburnoides Complex: An Initial Characterization of Sex Cascade Elements in the Context of a Hybrid Polyploid Genome

Abstract: BackgroundSex determination processes vary widely among different vertebrate taxa, but no group offers as much diversity for the study of the evolution of sex determination as teleost fish. However, the knowledge about sex determination gene cascades is scarce in this species-rich group and further difficulties arise when considering hybrid fish taxa, in which mechanisms exhibited by parental species are often disrupted. Even though hybridisation is frequent among teleosts, gene based approaches on sex determi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
17
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 80 publications
2
17
0
Order By: Relevance
“…1 D) The Squalius alburnoides complex, an Iberian cyprinid complex [see also Collares-Perreira et al, this issue] previously known as Leuciscus, Rutilus or Tropidophoxinellus, arose by hybridization involving females of Squalius pyrenaicus (P genome) and a species closely related to Anaecypris hispanica , which is responsible for its A genome [Pala et al, 2009]. In general, each S .…”
Section: Pre-equalizing Hybrid Meiosismentioning
confidence: 99%
“…1 D) The Squalius alburnoides complex, an Iberian cyprinid complex [see also Collares-Perreira et al, this issue] previously known as Leuciscus, Rutilus or Tropidophoxinellus, arose by hybridization involving females of Squalius pyrenaicus (P genome) and a species closely related to Anaecypris hispanica , which is responsible for its A genome [Pala et al, 2009]. In general, each S .…”
Section: Pre-equalizing Hybrid Meiosismentioning
confidence: 99%
“…The S. alburnoides hybrid complex (Cyprinidae) has been used as a model to study a variety of topics from polyploidy [Gromicho et al, 2006] to alternative reproductive strategies [Alves et al, 1998], genome interactions [Pala et al, 2008a], and sex determination and differentiation [Pala et al, 2008b[Pala et al, , 2009. However, key questions concerning reproductive development, sexual differentiation, pronounced female sex bias and the curious allmale lineage phenomenon are still without answers, and so, hermaphroditism could play an important role in some of these many unsolved cases.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, despite the fact that the molecular genetic mechanisms and the regulatory networks for sex determination have only recently started to be investigated in S. alburnoides [Pala et al, 2008b[Pala et al, , 2009, there are indications of sexual lability and environmental influence. Indeed, comparative studies on sex determination in distinct fish groups, revealed that the molecular mechanisms for sex determination can be temperaturedependent, even in species with a firm genotypic sex determination [reviewed in Ospina-Alvarez and Piferrer, 2008].…”
Section: Discussionmentioning
confidence: 99%
“…However, it is not known how sex is determined in S. alburnoides. Previous studies indicated that the mechanism of sex determination cannot be fully explained either by female or male heterogamety (Alves et al, 1998(Alves et al, , 1999 apparently being strictly a genetic mechanism (Pala et al, 2009). It seems that sex ratio in triploid forms is influenced by other Squalius genomes (C and P), either as a consequence of lower fitness of the AA, CAA/PAA males or CCA/PPA females and/or by the mechanism of sex determination.…”
Section: Biotype Compositionmentioning
confidence: 97%